Biochemical Features of Alcohol-Induced Liver Disease in Native Versus Non-Native Canadians - GY Minuk; W Thompson (Canadian Journal of Gastroenterology)
The medical records of 37 native and 40 non-native adult Canadians with alcohol-induced liver disease were reviewed in order to determine whether a biochemical pattern of bile ductular injury (increase in serum alkaline phosphatase levels) was more common and/or severe in native versus non-native Canadians. The results of this retrospective review revealed that serum alkaline phosphatase levels were markedly elevated (at least three tunes the upper limit of normal) in six of 37 (16%) native Canadians as compared to three of 40 (7.5%) non-native Canadians (PÃ0.05). Moreover, the mean peak serum alkaline phosphatase level for native Canadians was significantly higher than for non-natives (262±188 iu/L versus 197±101 iu/L, respectively, mean ± SD, PÃ0.05). Other liver enzyme and function tests were similar in the two groups. The study also revealed chat the mean duration of hospital stay for native Canadians with alcoholic hepatitis is significantly shorter than for nonnatives (8.5±6.0 versus 12.7±1 1.2 days, respectively, PÃ0.05) and the overall duration of hospital stay for patients with alcoholic liver injury has decreased in recent years from 26 days (May 1984-85) to 9.3 days (May 1987-88). The results of this study indicate that alcoholic liver disease in native Canadians is associated with higher serum alkaline phosphatase levels than in non-native Canadians.